Study on the early streamer emission mechanisms aided by laser ionization process - Ahmad, Hussein (Universiti Teknologi Malaysia, 2006)
Lightning, considered as a spectacular meteorological phenomenon, is one of the most fascinating events in the world. The preliminary scientific and systematic understanding of lightning phenomenon was first constituted by Benjamin Franklin in 1752 that used a kite in order to verify that lightning is really a stream of electrified air. Interestingly when Benjamin Franklin experimented with the electric kite, there were no very tall structures and high rise buildings like we observed today. However till today over more than 200 years the Benjamins lightning rod is still the most internationally accepted LAT. Many standards of LPSs have been published. Among which are the following standards: BS 6651 (British), NFPA 780(American), IEC 61024-1-2. These standards discuss and outline all important aspect of LPSs including design and methods for installing lightning terminal,bonding, and zone of protection calculation. However, these standards utilize Franklin rod concept for their lightning terminals. Even though these standards give some guidance and recommendations for installation of lightning protection, the standard can not assure the systems can provide 100% protection because there are evidences showing these systems can experience malfunctioning. A LAT tip can be damage by harsh environmental condition for instance due to acid rain that will affect on corona emission pattern. Corona developed on a tip of LAT have affect on the performance of the LAT. To study corona on the damage conventional lightning air terminal a new testing set-up was introduced. This testing set-up was completed with humidifier system, temperature control room and adjustable in high of cloud simulation disk. Indigenous Electric Field Mill system was developed. It was completed with a terminal to ADC before a PC (for display, analysis, and data collecting), a personal warning system, and an infra red unit (to initiate laser unit in LPS). The corona emission patterns on the damage convention LATs were acquired from the corona study. Further an empirical model by using dimension analysis was acquired. From this series of works an intensive reviewed published literature on lightning air terminal and lightning protection system was accomplished. A new model of LAT which is still conventional completed with free charge generator and laser unit was introduced.